Efek Segi Pelayanan, Harga, dan Lokasi Terhadap Kepuasan Konsumen Pada UMKM Cookies & Dessert By Me - Tiara Alvina Juliyanti; Yuni Putri Amelia; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to examine the effect of service quality, price, and location on customer satisfaction at Cookies & Dessert by Me UMKM. This study uses a quantitative approach through descriptive methods with observative. The results showed that simultaneously these three factors had a significant effect on customer satisfaction, while partially the service and price aspects had a greater influence than location. This study recommends that UMKM Cookies & Dessert by Me pay attention to service quality and affordable prices in maintaining consumer satisfaction, expanding marketing reach, and increasing collaboration with raw material suppliers to increase efficiency. The conclusion of this journal is that factors such as service and affordable prices are important elements in influencing consumer satisfaction, and MSMEs need to maintain and improve the quality of products and services on a regular basis.